IMPLEMENTATION OF INFORMATION COMMUNICATION TECHNOLOGIES (ICTS) IN THE PROCESS OF TEACHING AND LEARNING IN PRIMARY SCHOOLS IN ZIMBABWE: THE SURVIVAL STAGE RAGES ON. - Ruparanganda, Fenton; Tafirenyika, Joice (IJRDO- Journal of Educational Research, 2017)
This study explored the state of preparedness of primary schools to use ICTs during theprocess of teaching and learning and the extent to which the primary schools are using ICTsin Zimbabwe. Quality education in the 21st century can be achieved if teachers infused ICTsin the teaching and learning process. A survey of ten primary schools in Manicaland provinceindicated that separate computer rooms have been set up where pupils from grade three toseven received basic computer appreciation lessons once a week at allocated times from a‘specialist teacher’. Five teachers from each of the schools were interviewed, and ninetypercent (90%) of them were not computer literate. Only ten percent (10%) of the teachers hadacquired basic computer skills during teacher training and were all young teachers but did notuse computers in their day-to-day teaching. Traditional pedagogic practices continued as themeans of transmitting knowledge, skills and attitudes to pupils. The study also showed thatalthough teachers were aware of the various learning opportunities to be realised by ICTs,and computers in particular, they lack the knowledge and skills on how to use ICTs toenhance quality learning. Most schools do not have the necessary ICT equipment and Internetconnectivity is poor, non-existent or too expensive for most rural schools where the majorityof the students learn. The study recommends that the use of computers as a tool in theteaching and learning process in the classroom can make learning student centred and theteacher assumes a new role of becoming a facilitator.